Face and Content Validity of an Automated Vehicle Road Course and a Corresponding Simulation Scenario - Classen, Sherrilene; Wersal, James; Mason, Justin; Rogers, Jason; Sisiopiku, Virginia (Frontiers in Future Transportation, 2020)
Introduction: Automated vehicle use is rapidly expanding, globally. Florida is one of the leading states for researching, testing, implementing, and operating automated vehicles. Although driving simulators may create an opportunity to assess user behaviors related to automated vehicles, their use in this context is not well documented. Objectives: This study examined face and content validity of an on-road automated shuttle route and its congruence to a driving simulator scenario, representing the on-road route. Methodology: Face validity (i.e., clarity, understandability, congruence) was examined directly by members of the Institute for Mobility, Activity, and Participation. Content validity was assessed via a content validity index (CVI) based on inputs from experts who represented a variety of disciplines. These included computer and information science and engineering, transportation engineering, rehabilitation science, industrial and systems engineering, experimental psychology and driver rehabilitation science. Findings: Face validity resulted in feedback pertaining to traffic, environment, hazards, fidelity, and “other” recommendations. Six of the recommendations were used to enhance the simulator scenario. For content validity, the scale CVI was equal to .83, and was above the acceptable threshold of .80. However, on the item level, two items, i.e. traffic flow (I-CVI =.57) and seat direction (I-CVI = .67), were rated lower than anticipated. The ratings resulted in implementing enhancements to the driving simulator scenario. Conclusion: Automated vehicle on-road routes can be replicated in a driving simulator scenario but require a process of examining the face and content validity and refining the developed scenario, as need, to ensure reasonable accuracy.